Insights into nitrogen footprint accounting for products and application to an organic pig farm. (December 2021) - Niccolucci, V.; Marchi, M.; Neri, E.; Pulselli, R.M.; Bastianoni, S.; Marchettini, N.
Graphical abstract: Highlights: The N-Footprint accounting combines LCA principles and N impact assessment from IPCC.. The N-Footprint of "Mora Romagnola" pork is evaluated to illustrate the procedure. The Reactive nitrogen (Nr) released into the environment is 40.69 g Nr per pig L. W. The Reactive nitrogen (Nr) is released 38% in atmosphere, 27% in water and 35% in soil. A comparative analysis confirms the reliability of such accounting procedure. Abstract: The Nitrogen Footprint (N-Footprint) is the total amount of reactive nitrogen (Nr) released to the environment as a result of an entity's consumption patterns. N-Footprint assessments have mainly been consumer-oriented and country-sized, although concern has recently focused on single products, especially particular foods. While traditionally obtained from several software and/or calculators, the N-Footprint is here proposed to be evaluated by combining the Life Cycle (LCA) approach with a specific N based impact assessment modelling, as derived from Intergovernmental Panel on Climate Change guidelines. The theoretical procedure is then applied to a real livestock case study (the Mora Romagnola pig that provides high quality pork), mainly based on primary data. The total amount of Nr released was about 40 kg per pig (live weight), mainly due to direct components (i.e. manure management ∼ 85%). The results highlight the importance of more comprehensive and systematic quantification of emissions, especially direct ones that are neglected in the classical database and software. The Virtual N-Factor (VNF) was 2.3, which indicates that about 30% of N input by weight is incorporated in the meat, while most of it (∼70%) is dispersed to different environmental compartments (38% atmosphere, 35% soil, 27% water). A comparative analysis to check the reliability of outcomes and the robustness of the accounting procedure is also offered and show that these results are consistent with those reported in the literature for other pork products. The main benefit of this procedure is that it produces a unique aggregate result of the entity of human pressure on nitrogen cycle. This ensures a high comparability for results, transparency, and reproducibility of the method.